From Cork labour Activities to Co-Design Production. Azaruja Case Study - Reaes Pinto, Paula (2018)
The paper is centered on a social innovation design project which is being developed in the village of Azaruja, in the southeast of Portugal. The objective is to build a co-creative action with the local people, anchored on a local natural resource - cork - which is peeled from the cork oaks that characterize the place landscape. This project is focused on the labour activities related with cork that define the people and the place, which is understood in the present investigation in all its complexity, combining human, biophysical, geographical, economic, political, social, cultural, historical and ecological dimensions. The paper begins with Hannah Arendt's vita activa concept, which is crucial in distinguishing between the notions of labour, work and action. This is followed by some considerations about design anthropology in order to understand the methodology used in the co-creation process. Finally, the case study is described and examined its co-design methods.